1999
DOI: 10.1063/1.478113
|View full text |Cite
|
Sign up to set email alerts
|

The transition of chemisorbed hydrogen into subsurface sites on Pd(311)

Abstract: Articles you may be interested inStudy of the sticking of a hydrogen atom on a graphite surface using a mixed classical-quantum dynamics method

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
45
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 43 publications
6
45
0
1
Order By: Relevance
“…This finding is also expected because valence band electrons screen dipole-active hydrogen vibrations underneath the surfaces of metals (19).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…This finding is also expected because valence band electrons screen dipole-active hydrogen vibrations underneath the surfaces of metals (19).…”
Section: Resultsmentioning
confidence: 57%
“…Temperature programmed desorption, photoelectron spectroscopy, and neutron and He atom scattering data have provided indirect evidence for hydrogen occupying stable subsurface sites (6,(11)(12)(13)(14)19). These studies have indicated that the subsurface site is thermodynamically more stable than the bulk site and is of comparable stability to surface-bound hydrogen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The H 2 molecule dissociates into H atoms on the Pd surface. The H atoms are bound strongly at the hollow sites of the Pd surface even if at the room temperature [1][2][3][4][5][6]. After the adsorption on the surface, the H atom can penetrate into octahedral interstitial site of the Pd bulk via the subsurface sites.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic nanostructures represent promising research interests in the field of nanomaterials, such as catalysis (1,2), sensing (3,4), optics (5), therapeutics (6), and diagnostics (7), hydrogen storage (8), hydrogen purification (9) and photo-catalytic water-splitting (10) etc. Most of these applications depend largely on the unique optical and electronic properties of metals when their sizes are confined to nanoscale dimensions.…”
Section: Introductionmentioning
confidence: 99%